2014
DOI: 10.1097/ta.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality from femoral shaft fracture depends on the initial delay to fracture fixation and Injury Severity Score

Abstract: BACKGROUND Optimal surgical timing for definitive treatment of femur fractures in severely injured patients remains controversial. This study was performed to examine in-hospital mortality for patients with femur fractures with regard to surgical timing, Injury Severity Score (ISS), and age. METHODS The National Trauma Data Bank version 7.0 was used to evaluate in-hospital mortality for patients presenting with unilateral femur fractures. Patients were stratified into four groups by surgical timing (ST) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 32 publications
(35 reference statements)
0
19
0
2
Order By: Relevance
“…In high-income countries the annual incidence of femoral shaft fractures ranges between 8.2 and 23.9 per 100,000 people. Due to the high-energy mechanism, associated injuries are common in this patient population and the inhospital mortality has been reported to be approximately 1.4% [1][2][3]. In particular, musculoskeletal injuries to the ipsilateral limb, such as hip fractures, patella fractures, tibial plateau fractures, and ligamentous knee injuries have been reported to commonly occur in conjunction with high-energy femoral shaft fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In high-income countries the annual incidence of femoral shaft fractures ranges between 8.2 and 23.9 per 100,000 people. Due to the high-energy mechanism, associated injuries are common in this patient population and the inhospital mortality has been reported to be approximately 1.4% [1][2][3]. In particular, musculoskeletal injuries to the ipsilateral limb, such as hip fractures, patella fractures, tibial plateau fractures, and ligamentous knee injuries have been reported to commonly occur in conjunction with high-energy femoral shaft fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Para os próprios entrevistados a solução para este problema seria o maior investimento na quantidade e qualidade dos materiais. As repercussões da não realização deste procedimento imediatamente após a chegada ao serviço são: prolongamento do tempo de internação, maiores gastos hospitalares e maiores riscos de complicações sistêmicas inerentes às fraturas de ossos longos (10,(15)(16) .…”
Section: Resultsunclassified
“…In this study, elective surgery is almost all orthopedic surgery (74%). Cantu et al (10) reported that patients with multiple injuries will likely benefit from resuscitation before definitive stabilization of femur fractures, but early fixation after resuscitation is important. Thus early elective surgery may have to be considered after the emergent operation when the patient is recovered.…”
Section: Discussionmentioning
confidence: 99%